Environmental regulation under asymmetric information with type-dependent outside option - Jon Vislie (University of Oslo, Department of Economics, 2000)
We consider how a benevolent regulator should regulate a polluting export industry when the industry, having private information about its abatement efficiency, has an option to move its operations abroad, with a type-dependent outside option rent. The paper focuses on the case where outside option is negatively correlated with abatement efficiency, implying unilateral incentives for overstating abatement efficiency. Because lump-sum taxation is ruled out, rent will have a social cost which is also affected by foreign ownership to the industry. It is demonstrated that optimal regulation calls for excessive pollution among the participating types (relative to complete information), for the purpose of rent extraction, while types being excluded are the ones with the higher outside option (the least efficient types). We also demonstrate that with a higher foreign ownership share, the larger is the set of excluded types, while overpollution should be reduced.
Keywords: D62; D82; D78; L51; 330; Asymmetric information; environmental regulation; foreign ownership; type dependent participation constraints; Asymmetrische Information; Umweltpolitik; Theorie der Regulierung; Industriestandort; Standortwahl; Theorie